Vulval leiomyoma causing coital difficulty: report of two cases - Solaja, Olufemi A.; Fasubaa, Olusola B.; Ajenifuja, Olusegun K.; Adepiti, Clement A.; Adedeji, Nife O.; Adefidipe, Adeyemi A.; Ayodele, Solomon O.; Ndiwe, Augustine B.; Solaja, Oluwasola A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Leiomyoma is a smooth muscle benign tumor and it is a common benign lesion of the uterus in women of the reproductive age group with a prevalence of about 30%. Though the prevalence of uterine fibroid was 6.5% in Ile-Ife, and 8.5% of gynecological admissions in Ilesha, Nigeria, vulval leiomyoma is very rare and often misdiagnosed as Bartholin cyst or with other differentials like lipoma, etc. It is usually not considered a differential of vulval masses, but with detailed examination and with the use of investigative tools, the diagnosis can become clearer. This paper presents 2 cases of histologically diagnosed vulval leiomyoma seen at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC) between January 2017 and December 2021 with both patients complaining of coital difficulty. During this time, the prevalence of this lesion was calculated to be 0.092% of gynecology admissions and 0.17% of gynecological surgeries done in the hospital.